Intensive PhD course, IALE-Europe, “European Landscapes in Transition, the interplay between local and global drivers”, Manchester and Hathersage - Carvalho Ribeiro, Sónia (2014)
This PhD course will address the past and future of changing landscapes in Europe and will explore the novel approaches required for landscape research in order to understand the transitions taking place, and their multiple drivers and impacts. The course is centred in the landscapes which traditionally have been classified as rural and have at present multiple characteristics, as the fragmented periurban fringes, the productivist agricultural areas, vibrant residential communities or the most marginal rural peripheries. Particular attention is given to the interaction between rural and urban landscapes. Landscape will be considered from a spatial perspective especially the relationship between agriculture and other functions and other uses of the landscape, as well as the values resulting from these multiple uses. The discussions will develop the understanding of the changes taking place based on merging conceptual backgrounds from different perspectives.